The Influence of Corporate Governance Components on Banking Company Value with Disclosure in Sustainability Reports as a Mediating Variable - Ayu Intan Sari; Ni Made Dwi Ratnadi (International Journal Labs, 2025)
The value of banking companies in Indonesia has fluctuated despite consistent efforts to implement corporate governance principles. Furthermore, increasing pressure for transparency and accountability through disclosure in sustainability reports has become a key focus in assessing the impact of corporate governance practices on company value. This study aims to analyze the influence of corporate governance components on disclosure in sustainability reports and the value of banking companies. Furthermore, this study also analyzes the influence of corporate governance components on the value of banking companies, with disclosure in sustainability reports acting as a mediating variable. This study uses an associative quantitative approach, targeting banking companies listed on the Indonesia Stock Exchange (IDX) during the 2019–2023 period. The variables studied include institutional ownership, board of commissioners, audit committee, company size, sustainability report disclosure, and company value. Sampling was conducted using a purposive sampling technique, with a total of 95 observations. Data were collected through documentation and analyzed using path analysis to identify direct and indirect relationships between variables. The results of the study indicate that the audit committee has a positive and significant effect on sustainability report disclosure, while the board of commissioners, institutional ownership, and company size do not show a significant effect on the disclosure. Furthermore, institutional ownership and sustainability report disclosure variables have a positive and significant effect on firm value, while the board of commissioners, audit committee, and company size do not have a significant effect. The Sobel test results indicate that disclosure in the sustainability report does not significantly mediate the relationship between institutional ownership, the board of commissioners, and the audit committee on firm value. This finding indicates that the influence of corporate governance components on firm value is largely direct and is not effectively mediated by sustainability disclosure.